Community Assistance to Improve the Ability to Use Basic Unity and Virtual Reality - Herawati Yusuf; Novie Theresia Br. Pasaribu; Erwani Merry Sartika; Evan Adrian Adhi; Reynaldy Felicius Gunawan; Richard Setiawan; Dion Melvern Siswanto; Vieri Candhya Wigayha; Nathaniel Pius Winata; Markus Tanubrata; Rainisa Maini Heryanto (Journal of Innovation and Community Engagement, 2023)
During the pandemic of Corona Virus Disease 2019 (COVID-19) that hit Indonesia, all activities were very limited. Electrical Engineering Study Program of Universitas Kristen Maranatha was motivated  to share knowledge especially in the field of science about "Basic Unity and Virtual Reality (VR)" to the public. This has been realized through community service activities pursued by students and lecturers. VR refers to computer simulations that create images of the world that appear in human senses, in the same way as humans perceive the real world in reality. This community service used the Participatory Action Research (PAR) approach. From the results of a survey of community service activities that have been carried out, it is concluded that the success in providing mentoring to improve the ability of the community to use Basic Unity and VR online, is shown by the results of an increase in the score from an average of 5.85 before the activity, to 7.58 (from a total score of 10) after the activity. The community service committee team's service during the activity was also considered very good and worthy of being maintained in subsequent activities. Meanwhile, the implementation of providing teaching materials, the readiness of the trainers, and the implementation of organizing activities online, still need to be re-evaluated and improved in the future for better results.